An Analysis of Personality Disorder and Abnormal Sexual Behavior that Lead to Crime in Seduction in Death Novel by J. D. Robb - Mayangsari, Putri (LANTERN (Journal on English Language, Culture and Literature), 2017)
This thesis is derived from the author’s curiosity about the formation process of a personality. Therefore, the aims of this thesis are to learn about the importance of a childhood surrounded by healthy environment and criteria that determine the normality of a person’s personality. Two antagonist characters in a novel entitled Seduction in Death by J. D Robb are used as the objects of analysis. The writer uses library research as the method of the research. The writer also uses Psychoanalytic theory by Sigmund Freud and Sexual Disorder theory to concludes that a person’s personality has been formed since childhood and influenced by his or her childhood experiences and environment. Additionally, a person’s childhood experiences also affect whether his or her personality is analyze the objects involving the intrinsic and extrinsic elements of the novel. The writer considered normal or not